Exploring undergraduates’ money-management life: insight from an emerging economy - Sachitra, V; Wijesinghe, D; Gunasena, W. (YOUNG CONSUMERS, 2019)
Purpose – Undergraduates are expected to be future leaders responsible for business and nations. Given that sound financial decision-making is critical to their success in their careers and lives, it is important to understand the money-management behaviour of undergraduates. In the context of developing countries, the body of knowledge on money-management behaviour is dominated by functional financial literature and there is little research on factors beyond this. This study aims to fill this gap by exploring economic, social and psychological factors that influence money-management behaviour of undergraduates in a developing nation (Sri Lanka) and how undergraduates respond to theseinfluences. Design/methodology/approach – The study used a qualitative exploratory approach. Data collection was carried out using focus group discussions and individual interviews amongst undergraduates in a leadingSriLankanstateuniversity. Findings – The results indicate that undergraduates adopted both careful and risky moneymanagement approaches. The subthemes, specifically identified under economic, social and psychological factors, revealed how undergraduates responded to each of these factors and the influenceofcontextualandculturaldifferencesintheirmoney-managementbehaviour. Research limitations/implications – Findings of the study revealed the importance of promoting innovative educational strategies to change the dependability mindset of undergraduates and to promote stress-management strategies that will assist them to enhance their personalities and creativity in making financial decisions. Theoretical and practical implications and future research directions are provided. Originality/value – The literature scores in developing context are limited to exploring the existing pattern and the levels of the functional financial literacy. This study has deepened the authors’ understanding of how the developing context affects undergraduates’ response to the factors relating to their money-management behaviour. The findings from this study will be useful to government, financial institutions, educational institutions, parents and those who have a keen interest in encouraging healthy money-managementbehaviourinundergraduates.
Keywords: Qualitative approach, Undergraduates, Beyond ﬁnancial literacy, Money-management behaviour